Decline of Mean Initial Prednisone Dosage From 10.3 to 3.6 mg/day to Treat Rheumatoid Arthritis Between 1980 and 2004 in One Clinical Setting, With Long‐Term Effectiveness of Dosages Less Than 5 mg/day. Issue 5 (23rd April 2013) - Pincus, Theodore; Sokka, Tuulikki; Castrejón, Isabel; Cutolo, Maurizio
Abstract Objective To analyze prednisone treatment from 1980–2004 in 308 patients with rheumatoid arthritis (RA), including 75 monitored over 4–8 years and 73 monitored over >8 years, for initial dose, long‐term doses and effectiveness, and adverse events. Methods A database of all patients of a single rheumatologist included medications and Multidimensional Health Assessment Questionnaire (MDHAQ) scores at each visit. Proportions of patients whose initial prednisone dosages were >5, 5, or <5 mg/day were computed in 5‐year periods: 1980–1984, 1985–1989, 1990–1994, 1995–1999, and 2000–2004. Mean changes in MDHAQ function, pain, and Routine Assessment of Patient Index Data 3 (RAPID3) scores were compared in patients treated with <5 versus ≥5 mg/day of prednisone; scores and adverse events were analyzed in quartiles by treatment duration of ≤1, 1.1–4, 4.1–8, and >8 years. Results In the respective 5‐year periods, the mean initial prednisone dosages were 10.3, 6.5, 5.1, 4.1, and 3.6 mg/day, with >5 mg/day in 49%, 16%, 7%, 7%, and 3% of patients, 5 mg/day in 51%, 80%, 70%, 26%, and 10% of patients, and <5 mg/day in 0%, 4%, 23%, 67%, and 86% of patients. Most patients received early concomitant methotrexate after 1990, and prednisone <5 mg/day was maintained indefinitely. Patients treated with prednisone ≥5 mg/day had poorer clinical status as baseline and followup. MDHAQ scores improved similarly in patients treated with <5 or ≥5 mg/day. Primary adverse events were skin thinning and bruising. New hypertension, diabetes mellitus, and cataracts occurred in <10% of all patients, and <13% of those treated longer than 8 years. Conclusion The data suggest that many patients with RA might be treated effectively with initial and long‐term prednisone <5 mg/day, although further research and observational data are needed to characterize more fully effectiveness and safety.